Implementation Of Artificial Intelligence in Islamic Religious Education at Muhammadiyah Junior High School Kottabarat Surakarta - Intana Syifa Nabila; Mahasri Shobahiya (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2026)
Advances in Artificial Intelligence (AI) technology present both benefits an challenges for Islamic Religious Education (IRE), given the this subject is not only focused on cognitive achievement but also encompasses the development of students’faith, moral character, and spiritual values. This study aims to examine the implementation of AI in Islamic Religious Education at the Muhammadiyah Junior High School in Kottabarat, Surakarta. This study employs a qualitative approach, with data collection conducted through interviews with IRE teachers and the distribution of questionnaires to students, which were subsequently analyzed using the Miles and Hubermen model. The results indicate that the implementation of various al based platforms including Quizizz, Chatbot, Blooket, Canva, and educational videos has been systematically integrated into a single learning sequence, from planning to evaluation, and has been shown to significantly enhance student engagement, motivation, and the effectiveness of IRE instruction.  This study implies that the integration of AI in IRE has proven effective in increasing student engagement and learning effectiveness, thereby highlighting the need for an update to IRE learning theories and approaches that incorporate technology without neglecting spiritual values.